Exploring Pediatric Nurses’ Perspectives on Their Work Environment, Work Attitudes, and Experience of Burnout: What Really Matters? - Buckley, Laura; Berta, Whitney; Cleverley, Kristin; Widger, Kimberley (Frontiers in Pediatrics, 2022)
Background Pediatric nurses care for some of the most vulnerable patients in our healthcare system and are vulnerable to the impact of the stress of their work on their well-being. Burnout is a potential response to chronic interpersonal stressors and a negative work outcome linked to personal and professional consequences. A thorough understanding of the experience and factors associated with burnout in this population is an important part of developing interventions to mitigate or prevent this workplace outcome. Therefore, our study objectives were to: (1) explain and expand our understanding of pediatric critical care nurses experience of burnout in relation to their work environment and work engagement; (2) provide recommendations for nursing administrators to improve nurses’ work environment, work attitudes, and work outcomes. Methods A convenience sample of pediatric critical care nurses from a large pediatric quaternary care hospital in Ontario, Canada were invited to participate in this second phase of a sequential explanatory mixed-methods study. Semi-structured interviews were conducted, with and main themes and subthemes distilled through the method of interpretive description. Results A total of 18 PICU/CCCU/NICU nurses participated. Derived themes included the experience and identification of burnout, including its prevalence and elusiveness. Their experiences of quality of work-life included themes such as compensation, emotional support at work, respect, their professional identity, and spill over into home life. They discussed components of work engagement, including the work itself, investment into their growth and development, and the meaning of their work. The self-care subthemes included the importance of preparation and recovery, and the use of physical and mental separation as a preservation strategy. The participants’ recommendations for strategies to mitigate burnout were also summarized. Conclusion Burnout is a complex and regularly occurring experience for pediatric critical care nurses. Although the experience may be difficult to self-identify, the impacts on the individuals are profound. Further research and organizational support are needed to test practical and evidence-based interventions to improve the well-being of this population.